สมรรถนะที่พึงประสงค์ของนักศึกษาฝึกงานครูอาชีวศึกษาระดับปริญญาตรี สาขาวิชาช่างเชื่อมโลหะ ที่สอดคล้องตามความต้องการของสถานอาชีวศึกษา สปป. ลาว: Desirable Competencies of the Student Teaching Vocational Internship for the Bachelor’s Degree in Metal Welder in Accordance with the Needs of Vocational Schools in Lao PDR - Xonh Xobvong ซน ซอบวง; Teerapun Saeheaw ธีราพรรณ แซ่แห่ว (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2022)
The objectives of this survey research were to: (1) study on the desirable competencies of the student teaching vocational internship for the Bachelor’s degree in metal welder in accordance with the needs of vocational schools in Lao PDR and (2) compare the opinion of the administrators and the operators on the desirable competencies of the student teaching vocational internship for the Bachelor’s degree in metal welder in accordance with the needs of vocational schools in Lao PDR. The sample was 90 people who work at vocational schools in Lao PDR, selected by using purposive sampling technique. The research used two sample groups. The first group consisted of vocational school administrator at four levels: vocational school directors; vice-directors; department heads and branch heads. The second group included teachers who provided welder instructions. The instruments used were questionnaire which divided into two parts. The first part is the questionnaire of professional standards for teachers consisted of three parts: professional attributes, professional knowledge and understanding and professional skills. The second part is the questionnaire of competency standards for welders consisted of three parts: followed safety rules, maintenance and Shielded metal arc welding (SMAW). The data were analyzed by descriptive statistics including Frequency, Percentage, Mean, and Standard Deviation. The findings of this research were as follows: (1) The needs assessment of professional standards for teachers was at high level in both sample groups. According to administrators’ opinions, the listed mean scores in order from the highest to the lowest included professional knowledge and understanding, professional skills and professional attributes. For operators’ opinions, the listed mean scores in order from the highest to the lowest included professional knowledge and understanding, professional skills and professional attributes. (2) The needs assessment of competency standards for welders was at high level in both sample groups. According to administrators’ opinions, the listed mean scores in order from the highest to the lowest included follows safety rules, SMAW and maintenance. For operators’ opinions, the listed mean scores in order from the highest to the lowest included SMAW, follows safety rules and maintenance.